Sebaran dan Kondisi Karang Batu di Perairan Kecamatan Wori, Sulawesi Utara - Souhoka, Jemmy (Universitas Atma Jaya Yogyakarta, 2010)
Hard or stony coral is one important component to structure the coral reef ecosystem and play a significant role for its marine life and its surrounding. Therefore, the condition of reef ecosystem needs to be maintained. Research on stony coral condition and distribution in waters of Wori Village, North Sulawesi, was conducted in April 2008. Line Intercept Transect was applied to assess the coral condition. A 50 m line transect was set on the 5 - 7 m depth horizontally coastal line with assumption that in this depth, coral growth well. The results of this study show that the condition of coral was between 1,00 and 53,44% indicating the condition ranged from bad to good category. Stony coral distribution was found up to 20 m depth, with the highest diversity and evennes indices were 1,06 at station 3, and 0,56 at station 4, respectively. Numbers of stony coral were 99 species belonging to 40 genus and 14 families.